Female Urinary Retention in the Young and Elderly: A Case Report and Review of Literature - Hakim Gharib Bilal; Saw Ohnmar; FS Malhi; SH Syed Rahim; A.W.Noraziana; A. Suhaiza; R. Roszaman; A. Mokhtar (Asian Journal of Medicine & Health Sciences, 2018)
Urinary retention rarely affects women. In obstructive retention the source must be determined and treated to allow the patient to void normally. A common anatomic cause of urinary retention is extrinsic compression due to a pelvic mass. In addition, obstruction can also be seen in women with pelvic organ prolapse. Haematocolpos and uterine fibroids have also been documented as causes of acute urinary retention. The following cases of female urinary retention highlight the need to consider haematocolpos in the adolescent girl who has not attained menarche and fibroids in the older female.